Increasing Warehouse Efficiency Using ABC Analysis and FIFO System a Case Study of a Private Company in Rayong Province - วงคมะณี วชิรศักดิ์; พิศุทธิ์เกียรติ เจนจิรา; บัวพร นาตาลี; ทาปั๋น ณัฐมน (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to reduce the time to search for raw materials, reduce the deterioration of raw materials, improve the efficiency of storage in the warehouse, and reduce the chance of picking similar products incorrectly. The data was collected and the raw material data was used to classify the raw materials in order to manage the inventory to the greatest benefit and to separate the types of products to make it easier to count the products correctly and accurately. The improvement and correction to meet the standards and the actual products in the system are the same. Because the ABC analysis and FIFO system principles were used to divide the product placement area into the ABC format by placing labels on the shelves to clearly show the product name, product code, and barcode to make the products clearly visible. The warehouse staff were also informed not to place products on the floor to block the product aisle, making it convenient to pick and take out products, which made picking raw materials more efficient.